Selling your house : Nolo's essential guide - Bray, Ilona M., 1962- (Nolo, 2025)
"This book takes the reader through the process of selling their house from start to finish. Discusses setting a price that will attract buyers, finding the right real estate agent, determining which repairs and upgrades pay off, making legally required disclosures to buyers, evaluating purchase offers, and negotiating and closing escrow successfully. This book also provides tips from industry pros--including real estate agents, attorneys, home stagers, and more--as well as stories from home sellers"--